Chronology and documentary handbook of the State of Nebraska - Vexler, Robert I. (Chronologies and documentary handbooks of the States ;, 1978)
Contains a chronology of historical events in Nebraska, a biographical directory, the first State constitution, and selected documents pertinent to Nebraska history.